2020
DOI: 10.14814/phy2.14343
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and transforming growth factor β1 regulation of long non‐coding RNA transcriptomes in human pulmonary fibroblasts

Abstract: One of the key characteristics of idiopathic pulmonary fibrosis (IPF) is accumulation of excess fibrous tissue in the lung, which leads to hypoxic conditions. Transforming growth factor (TGF) β is a major mediator that promotes the differentiation of fibroblasts to myofibroblasts. However, how hypoxia and TGFβ together contribute the pathogenesis of IPF is poorly understood. Long non‐coding RNAs (lncRNAs) have regulatory effects on certain genes and are involved in many diseases. In this study, we determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 63 publications
4
20
1
Order By: Relevance
“…The interaction between hypoxia and other factors involved in IPF development has also been reported. For instance, hypoxia and TGF-β act synergistically in regulating a number of mRNAs and lncRNAs in lung fibroblasts, potentially contributing to IPF pathogenesis [ 288 ]. Compared to wild-type mice, bleomycin-treated mice deficient of the ER stress-regulated transcription factor C/EBP homologous protein (CHOP) are protected from the exacerbated lung fibrosis elicited by hypoxia [ 289 ].…”
Section: Cellular and Molecular Mechanisms In Ipfmentioning
confidence: 99%
“…The interaction between hypoxia and other factors involved in IPF development has also been reported. For instance, hypoxia and TGF-β act synergistically in regulating a number of mRNAs and lncRNAs in lung fibroblasts, potentially contributing to IPF pathogenesis [ 288 ]. Compared to wild-type mice, bleomycin-treated mice deficient of the ER stress-regulated transcription factor C/EBP homologous protein (CHOP) are protected from the exacerbated lung fibrosis elicited by hypoxia [ 289 ].…”
Section: Cellular and Molecular Mechanisms In Ipfmentioning
confidence: 99%
“…TNFα directly induces the expression of TGF-β [25]; therefore, in the early stage of the bleomycin-induced rat model, the expression of TGF-β1 was also high in the lung tissue. TGF-β1 is a key direct fibrosis factor that can promote the transformation of pulmonary fibroblasts into myofibroblasts, produce more matrix protein components, and release them into extracellular matrix, thus leading to the occurrence and development of PF [26,27]. Furthermore, TGF-β1 signaling can induce phosphorylation and activation of JAK2, thereby activating the JAK2/STAT3 signaling pathway, and this vicious circle amplifies the inflammatory response and pulmonary fibrosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, lncFENDRR represses fibroblast activation by binding iron‐responsive element‐binding protein 1 to control iron levels and by competing with the pro‐fibrotic miR‐214 92 . From the microenvironment, Senavirathna et al 93 . have revealed that hypoxia and TGFβ1 treatment causes significant changes in 669 lncRNAs compared to 150 lncRNAs in a TGFβ1 alone group and 222 lncRNAs in a hypoxia alone group using an RNA sequencing method.…”
Section: Lncrna Regulates Pulmonary Fibrosis By Targeting Not Only Prmentioning
confidence: 99%
“…have revealed that hypoxia and TGFβ1 treatment causes significant changes in 669 lncRNAs compared to 150 lncRNAs in a TGFβ1 alone group and 222 lncRNAs in a hypoxia alone group using an RNA sequencing method. Among these lncRNAs, lncFENDRR is downregulated by hypoxia and TGFβ1 in human pulmonary fibroblasts 93 . lncMalat1can also sponge miR‐503 to control EMT through the PI3K signal pathway in silica‐induced pulmonary fibrosis 84 .…”
Section: Lncrna Regulates Pulmonary Fibrosis By Targeting Not Only Prmentioning
confidence: 99%